Evaluation of Beef Meat Quality at Slaughterhouse in Kendari City - Jurnal Peternakan Integratif (Talenta Publisher, 2020)
. This study aims to find out whether DFD (Dark, Firm, and Dry) and PSE (Pale, Soft, and Exsudative) happen/ occur to Bali Cattle Carcas slayed in Anggoeya Animal Slaugtherhouse in Kendari City. This study is useful to give information about the meats’ DFD and PSE cases and carcas quality at Anggoeya Slaugtherhouse in Kendari City. The sample of this study are 6 bulls and 6 cows taken from slaugtherhouse in Kendari City. The obtained data was, then, analyzed descriptively based on the mean and deviation standard (χ ± SD).The variables observed in this studyincludes PH measurement for 1 – 6 hours after slashing, color, loss of mass, texture, hardness, and humidity. The meats were found to be around normal PH 5.55 – 5.73. Based on the color score AUS_MEAT Colour, the color of the meats were around the score of 4 – 5, loss of mass were around 30,64 – 43,28%. Based on panelist judgement, most of the meats texture were scored 3 or were in moderate level. Most of the meats’ elasticity were scored 3 or were rather soft, while most of the meats’ humidity were scored 3 or moderate (62.50%). On the meats produced by the Animals Slaugtherhouse in Kendari City, no changes to DFD (Dark, Firm, and Dry) or PSE (Pale, Soft and Exudative) was found.